Persuasive strategies in top TikTok breast cancer videos: a rhetorical analysis - Nour Mheidly; Priyanka Kundu; Marilyn Facey (Discover Social Science and Health)
Abstract TikTok is a user-driven video platform that fosters communication, engagement, and interactivity among its users. Health influencers leverage TikTok to promote and share medical advice on various health topics, including breast cancer. This study investigates the factors that contribute to the persuasiveness of cancer influencers on TikTok by analyzing the 25 most popular breast cancer videos. The analysis employs a rhetorical framework consisting of three primary appeals: ethos (credibility, expectation, and reference), pathos (tone, emphasis, and engagement), and logos (clarity, consciousness, and arrangement). Each rhetorical appeal encompasses three characteristics that help elucidate the influencers’ persuasive communication strategies. The study identifies four key themes related to these persuasion strategies: the integration of ethos, pathos, and logos within individual videos; the use of medical expertise to enhance credibility; the strategic utilization of TikTok’s unique features to effectively convey messages; and the role of TikTok as a platform for informing, educating, and raising awareness about breast cancer.